In vitro inhibition of multi-drug resistant pseudomonas efflux pump by xylopia aethiopica (dunal) A. rich (2021)
Global health is under constant threat due to antimicrobial drug resistance. Bacterial Infections caused by Pseudomonas aeruginosa are of importance because of their antibiotics resistance. This study aimed at evaluating the effects of extracts of Xylopia aethiopica (XA) on multidrug-resistant (MDR) Pseudomonas isolates. Fresh samples of XA leaf, stem bark and roots were collected from the botanical garden, University of Ibadan, Nigeria. Dried and pulverized samples were extracted with methanol and partitioned into n-hexane, dichloromethane and ethyl acetate. Phytochemical screening of the extracts was performed by standard methods. Antimicrobial activity and synergistic interaction were determined using microdilution and checkerboard broth dilution methods, respectively. The results revealed that crude methanol extracts of XA leaf, stem bark and root significantly (p<0.05) inhibited the growth of all tested MDR Pseudomonas isolates at 10 mg/mL. At 1 mg/mL, the ethyl acetate fraction of the leaf, and dichloromethane fraction of the roots produced clear zones of inhibition of 12 – 20 mm, and minimum inhibitory concentrations (MICs) of 1 μg/mL and 0.5 mg/mL, respectively. The modulation factor (MF) of ciprofloxacin, dichloromethane fraction of XA roots and ethyl acetate fraction of XA leaf were 4, 8, and 4 on MDR isolates E01006, OAU058 and P. aeruginosa ATCC 27853, respectively. In all tested isolates, but not E01006 and E01024, the fractional MICs of ciprofloxacin/ethylacetate fraction of XA leaf extract combination was not significantly different (p>0.05) compared with ciprofloxacin/verapamil combination. In conclusion, the root and leaf fractions Xylopia aethiopica that demonstrated antimicrobial activity against MDR P. aeruginosa and synergised with ciprofloxacin have the potential to rejuvenate the antimicrobial activity of ciprofloxacin in MDR P. aeruginosa.